Penerapan Asas Piercing The Corporate Veil: Perspektif Tanggung Jawab Direksi Perseroan Terbatas - Putri Sari Harahap; Tumanggor Tumanggor (Postgraduate of Jayabaya University, 2015)
Piercing The Corporate Veil principle is a common law doctrine that teaches about the veil special breakout company (corporate veil) covering the Board of Directors and other organs in running the company does not fit or have violated the principle of fiduciary duty (good faith) to the intent and purpose of the company.This type of research in this thesis is a normative legal research means tend to use secondary data in the form of primary legal materials, secondary law and tertiary legal materials. To collect the data in this research is a stud y done by the descriptive analysis. The resulted in losses for both the company and third parties, First Defendant's actions can be categorized as a tort (onrechtmatige daad) under Article 1365 of the Civil Code. In the verdict the judge in his ruling has been applying the principle of piercing the corporate veil but does not necessarily resolve the matter of debts between the Compa- ny (Plaintiff) with rights holders of promissory notes